Study of the production of [delta]0b and B[bar]0 hadrons in pp collisions and first measurement of the [delta]0b → J/[psi]pK- branching fraction* - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Grillo, Lucia; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Chinese physics. C, High energy physics and nuclear physics, 2016)
The product of the differential production cross-section and the branching fraction of the decay is measured as a function of the beauty hadron transverse momentum, pT, and rapidity, y. The kinematic region of the measurements is pT < 20 GeV/c and 2.0 < y < 4.5. The measurements use a data sample corresponding to an integrated luminosity of 3fb−1 collected by the LHCb detector in pp collisions at centre-of-mass energies in 2011 and in 2012. Based on previous LHCb results of the fragmentation fraction ratio the branching fraction of the decay is measured to bewhere the first uncertainty is statistical, the second is systematic, the third is due to the uncertainty on the branching fraction of the decay B̅0 → J/ψK̅*(892)0, and the fourth is due to the knowledge of . The sum of the asymmetries in the production and decay between and is also measured as a function of pT and y. The previously published branching fraction of , relative to that of , is updated. The branching fractions of are determined.
*The LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, S. Braun, A. Comerma-Montells, M. De Cian, S. Esen, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kecke, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, U. Uwer, M. Vesterinen, A. Zhelezov [und 698 weitere Personen]
Im Titel sind "delta" und "psi" als griechische Buchstaben dargestellt
Im Titel steht der Buchstabe B mit einem Oberstrich
Im Titel ist der Buchstabe b tiefgestellt
Im Titel ist die Zahl "0" hochgestellt